2009
DOI: 10.2165/00002512-200926030-00003
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Stroke Prevention Strategies for the Oldest Patients

Abstract: Older adults are not only at higher risk of experiencing stroke, but also have multiple co-morbidities that make treatment for secondary stroke prevention challenging. Very few clinical trials specifically related to secondary stroke prevention treatment efficacy have focused on the oldest-old (≥85 years) and, therefore, evidence-based recommendations for treatment specific to this population are not available. Some of the special considerations for stroke prevention treatments in older patients include carefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 146 publications
0
18
0
1
Order By: Relevance
“…2,7,19 It is the leading cause of death only next to cancer. 11,29,33 There are three types of strokes, which include Ischemic (88%) Hemorrhagic (12%) and Transient (rare type). 6,8,18 According to WHO, 15 million people worldwide suffer from stroke each year.…”
Section: Introductionmentioning
confidence: 99%
“…2,7,19 It is the leading cause of death only next to cancer. 11,29,33 There are three types of strokes, which include Ischemic (88%) Hemorrhagic (12%) and Transient (rare type). 6,8,18 According to WHO, 15 million people worldwide suffer from stroke each year.…”
Section: Introductionmentioning
confidence: 99%
“…For older men with a history of MI, the probability of having a recurrent stroke was 6.761 times that for stroke patients without such a history 16,17 . Similarly, in elderly men, DM was also a risk factor for recurrent stroke 18,19 . However, by contrast, our study found that in elderly men, HTN was not a strong risk factor for stroke recurrence.…”
Section: Discussionmentioning
confidence: 92%
“…Although from this research it might seem that making substantial changes in lifestyle is not important, it is important to note that most of the biologic mechanisms by which different factors influence risk of a first time stroke are also likely to have effect on risk of recurrent stroke. However pharmacological therapy and life modifications are recommended for all patients who have had an ischaemic stroke or transient ischaemic attack (Bushnell and Colon-Emeric, 2009). …”
Section: Previous Researches On Stroke Scoring and Risksmentioning
confidence: 99%